Leadership Style and Employee Performance in Nepalese Enterprises - Devakota, Surya Prasad; Rai, Bharat; Sharma, Bhanu Bhakta (Nepal Journal of Multidisciplinary Research, 2026)
Background: Leadership style is a vital factor influencing the performance of employees; however, there is little scientific literature on how different leadership styles jointly affect employee performance, especially in the public sector organizations of Nepal. Objective: The present study analyzes the effects of six leadership styles, which include transformational, charismatic, transactional, democratic, autocratic, and bureaucratic styles, on employee performance, moderated by gender. Methodology: The study adopted a quantitative, cross-sectional design where data collection was done through a survey of 310 academic staff members from 50 organizations in Nepal. Data analysis techniques used were descriptive statistics, correlation analysis, and regression analysis. Reliability of the test instruments was checked through Cronbach’s alpha with an overall value of α=0.847. Findings: Democratic leadership (r=0.234, β=0.166), charismatic leadership (r=0.220, β=0.212), and transformational leadership (β=0.245) significantly positively influenced performance. On the other hand, bureaucratic leadership exhibited the highest negatively correlated relationship with performance (r=-0.725, β=-0.180), whereas autocratic leadership showed the lowest negative relationship (r=-0.161). Little difference was observed between genders, but female staff experienced more creativity restrictions under transactional leadership. The regression model proved to be significant (F=23.162, p<0.001). Conclusion: The democratic and transformational styles of leadership are beneficial for employee performance, whereas the bureaucratic and autocratic styles have negative impacts on it. Environmental influences affect leadership success in Nepali public colleges. Implications: Organizations need to encourage participative leadership methods, reduce bureaucratic behavior, and consider gender-related perceptual distinctions in leadership training programs.